HARDWARE SUPPORT PROCEDURES FOR ASYMMETRIC AUTHENTICATION OF THE INTERNET OF THINGS - Петро Сергійович Клімушин; Тетяна Миколаївна Соляник; Олександр Олександрович Можаєв; Віталій Вікторович Носов; Тетяна Петрівна Колісник; Василь Вікторович Янов (Сучасний стан наукових досліджень та технологій в промисловості)
Subject of research: procedures of asymmetric authentication of Internet of Things nodes to ensure the highest level of security using cryptographic chips. The aim of the article is to study the ways of potential use of cryptographic chips to ensure secure authentication of Internet of Things sites using asymmetric cryptography procedures. The article solves the following tasks: analysis of hardware support technologies for asymmetric cryptography of the Internet of Things; definition of secure procedures for asymmetric authentication of Internet of Things sites and their constituent elements: creation of certificates, verification of public and private keys. Research methods: method of structural and functional analysis and design of complex systems, methods of identification and authentication of information objects, cryptographic methods of information protection, methods of security analysis of distributed information systems. The novelty of the study is the analysis of hardware support technologies for asymmetric cryptography of Internet of Things with cryptographic chips and the definition of structural and functional schemes for the implementation of procedures for asymmetric authentication of Internet of Things. Distinctive features of the provided asymmetric authentication schemes and procedures are: ensuring an increased level of information security through secure storage of cryptographic keys, digital signatures, certificates, confidential data in a novelty security environment protected from external attacks and no need to store private keys on the host side. The results of the work are procedures and schemes of application of cryptomicrops of asymmetric authentication to ensure the protection of Internet of Things. Analysis of the functioning of the presented schemes allowed to draw the following conclusions. The proposed structural and functional schemes for the implementation of procedures for asymmetric authentication of Internet of Things using cryptographic chips give the user an easy opportunity to implement cryptography without expertise in this field. These chips use the ECDSA digital signature computing and verification hardware with elliptical curve advantages, as a proven and reliable authentication algorithm, and the ECDH symmetric encryption session key generation unit. The provided schemes and procedures support three components of information security, namely: confidentiality, integrity and authenticity of data. Examples of potential applications of the provided schemes and procedures can be implemented using any asymmetric authentication chip, but it is recommended that they be used to generate encryption session keys and where digital signatures are required to verify data and code for integrity and authenticity.